TRADISI KEISLAMAN DALAM BINGKAI MAZHAB: STUDI KOMPARATIF MAROKO DAN INDONESIA BERDASARKAN KONTEN AKUN INSTAGRAM @AQSHOHAZIQ - Azrel Pamula, Alma; Ayu Saputri, Isna; Mutsirotunnafisah; Ulfa, Lailatul; Siyono (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2025)
This study examines how Islamic traditions in Morocco and Indonesia are represented through the Instagram account @aqshohaziq, and how these representations illustrate the interplay between madhhab, culture, and religious practices. Employing a qualitative descriptive-comparative approach, this research integrates digital ethnography and thematic content analysis to interpret photos, videos, captions, and user interactions related to religious rituals, Qur’anic literacy, and socio-religious structures. The findings indicate that Morocco embodies a highly institutionalized model of religiosity rooted in the Maliki madhhab, Sufi heritage, and state-centered authority, resulting in disciplined and uniform religious expressions. In contrast, Indonesia presents a more community-driven and culturally diverse religious landscape, shaped by the Syafi‘i madhhab and embedded local traditions. The study concludes that social media functions not merely as a documentation platform but also as a dynamic space where Islamic identities are negotiated and represented to a global audience. These insights enrich digital Islamic studies and comparative madhhab research by demonstrating how religious practices adapt, converge, and diverge across different cultural settings.